Analysis Of Critical Thinking Skills and Learning Independence of Elementary School Students - Monica Astriyanti Sukardi; Reiska Nur Tahbaria; Uni Maelani (CV. Akademi Merdeka, 2025)
The purpose of this observation is to analyze how students' thinking skills are when viewed from the perspective of students' learning independence. This research was conducted in class 4 of SDN Penggung Utara. The research subjects were 38 students consisting of 12 male students and 26 female students. This observation used a qualitative research type. The instruments used in this study were a learning independence questionnaire, and a written test of conceptual understanding consisting of 7 descriptive questions and interviews with homeroom teachers. Data analysis used includes data presentation and drawing conclusions. The results of this study state that students with critical thinking skills of 81-100% are included in the very good category.